Young children's behavioral and neural responses to peer feedback relate to internalizing problems. (April 2019) - Morales, Santiago; Vallorani, Alicia; Pérez-Edgar, Koraly
Abstract: Despite the importance of peer experiences during early childhood for socioemotional development, few studies have examined how young children process and respond to peer feedback. The current study used an ecologically valid experimental paradigm to study young children's processing of peer social acceptance or rejection. In this paradigm, 118 children (50% boys; Mage = 72.92 months; SD = 9.30; Rangeage = 53.19–98.86 months) sorted pictures of unknown, similar-aged peers into those with whom they wished or did not wish to play. They were later told how these peers sorted them, such that in half of the cases the presumed peer accepted or rejected the participant. When rejected children reported more distress (sadness), they were slower to rate their affective response, and exhibited increased mid-frontal EEG theta power, compared to when accepted. Moreover, we found that children's affective responses and EEG theta power for rejection predicted internalizing problems, especially if they displayed an attention bias to social threat. Our results further validate and illustrate the utility of this paradigm for studying how young children process and respond to peer feedback.